The Effect of STEM-Based Mathematics Learning on Critical Thinking Ability of Elementary School Students - Ahmad Sahabudin; Parhaini Andriani; Muhammad Ghazali (Jurnal Pendidikan Matematika (JPM), 2024)
Critical thinking skills are one of the most important 21st century skills for students, and the fact that students' abilities are lacking due to their involvement in the classroom is critical thinking skills. The purpose of this research is to prove that teaching mathematics concepts in STEM schools has or does not have an effect on the critical thinking skills of elementary school students. This research is qualitative with a quasi-experimental type. This study involved 20 Grade V students at SDIT An-Nujaba' Mataran who were included as a sample selected by the saturated sampling technique, the instrument used in this study was a critical thinking ability test. The analysis technique uses the t-test (paired sample t-test). The results of this study indicate that there is a p-value = 0.000 which indicates a significant difference before and after the application of STEM-based mathematics learning. The findings of this study indicate that, with the support of STEM mathematics education, students' critical thinking skills have a significant effect. The research of STEM-based learning in critical thinking skills.